2004
DOI: 10.1007/s10565-004-1471-1
|View full text |Cite
|
Sign up to set email alerts
|

Low-level arsenite activates the transcription of genes involved in adipose differentiation

Abstract: In this study we analyzed gene expression in 3T3-F442A pre-adipocyte cells that differentiate in the presence of micro-molar arsenate concentration. Two concentrations of arsenite (As2O3, 0.25 micromol/L and 0.5 micromol/L) were applied for three days with and without insulin (170 nmol/L) and gene expressions were evaluated by quantitative RT-PCR. The genes included genes of oxidative-stress responses: heme-oxygenase-1 (HO1) and the hypoxia inducible factor 1a (HIF1alpha), genes of cell-cycle: c-jun and Kruppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Low-dose As 2 O 3 (0.25 and 0.5 μM) has been reported to activate the transcription of genes involved in adipose differentiation (Salazard et al 2004). In contrast, Wang et al (2005) reported that As 2 O 3 (3 μM) did not induce apoptosis but inhibited differentiation of preadipocyte 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose As 2 O 3 (0.25 and 0.5 μM) has been reported to activate the transcription of genes involved in adipose differentiation (Salazard et al 2004). In contrast, Wang et al (2005) reported that As 2 O 3 (3 μM) did not induce apoptosis but inhibited differentiation of preadipocyte 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The features of diabetes mellitus most commonly observed in arsenic-exposed individuals are similar to non-insulin-dependent diabetes mellitus or Type 2 diabetes [14]. Although the biological mechanisms responsible for arsenic-induced diabetes mellitus are largely unknown, recent evidence suggests that the trivalent arsenicals may suppress insulin-stimulated glucose uptake by interfering with mobilization of glucose transporters in adipose cells [36], as well as interfering with transcription factors involved in insulin-related gene expression [37]. …”
Section: Discussionmentioning
confidence: 99%
“…In 3T3-L1 pre-adipocyte cells, which differentiate in the presence of micro-molar arsenic, arsenite treatment induces the expression of KLF5 [89]. A role of KLF5 in adipose differentiation was further demonstrated in a mouse model, where neonatal heterozygous KLF5 knockout mice exhibit a marked deficiency in white adipose tissue development [46].…”
Section: Differentiationmentioning
confidence: 98%